Gender dimensions of agricultural innovation awareness and adoption - Haglund, Eric; Bernier, Quinn; Bryan, Elizabeth; Kovarik, Chiara; Kristjanson, Patricia; Meinzen-Dick, Ruth S.; Quiros, Carlos; Ringler, Claudia; Rufino, Mariana; Silvestri, Sylvia; Twyman, Jennifer (International Food Policy Research Institute, 2014)
The 3-year startup phase of the BioSight project envisions the development of “models, tools, and problem-focused analytics” to contribute to the project’s larger goal of establishing stronger micro-level and spatially explicit foundations to advancing the state of bioeconomic modeling. The project aims to devote particular attention to the issue of gender, and the question of how BioSight’s new models and tools can better account for the various ways the gender of resource users affects decisions about agriculture, natural resource management, and technology adoption. This paper discusses some of the conceptual issues involved in more fully accounting for gender when considering agricultural innovation adoption and presents a brief empirical analysis to illustrate the challenges of applying these insights to analytical methods.